Librarians - Gorman, Jacqueline Laks, 1955-; Gorman, Jacqueline Laks, 1955- (New York, NY : Gareth Stevens Pub., 2010)
A simple introduction to the work of librarians in a library.
"Leveled reader: social studies"--Cover p. 4.
Original ed. published: Librarian. Weekly Readers Books, 2003.
Includes bibliographical references (p. 23) and index.
Keywords: Librarians -- Juvenile literature; Libraries -- Juvenile literature